Meningkatkan Hasil Belajar Matematika Melalui Pembelajaran Bermakna Berbantuan Media Papan - Nina Rahayu; Fitri Anggun Dersila; Raudatul Husna (TA'DIBAN, 2026)
This study was motivated by the low mathematics learning outcomes of third-grade students at SD Negeri 2 Seulalah in division, as indicated by the large number of scores below the minimum passing grade. Students had difficulty understanding concepts and solving word problems because the material was abstract, their initial abilities varied, their motivation was low, and the learning was not contextual. This study aims to determine the effect of meaningful learning aided by blackboard media on learning outcomes. The method used is a quasi-experiment with a non-equivalent control group design. The pretest and posttest data were analyzed using an independent sample t-test. The results showed a significant increase in the experimental class (28.00 to 78.25) compared to the control class (22.33 to 46.33) with a significance of <0.05. Meaningful learning aided by board media was effective in improving students' understanding and engagement.